Crystal structure of halofuginone hydrobromide, C16H18BrClN3O3Br. Issue 1 (March 2023) - Kaduk, James A.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of one form of halofuginone hydrobromide has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional theory techniques. Halofuginone hydrobromide crystallizes in space group P2 1 (#4) with a = 8.87398(13), b = 14.25711(20), c = 15.0153(3) Å, β = 91.6867(15)°, V = 1898.87(4) Å 3, and Z = 4. The crystal structure consists of alternating layers (parallel to the ab -plane) of planar and nonplanar portions of the cations. N–H⋯Br and O–H⋯Br hydrogen bonds link the protonated piperidine rings and bromide anions into a two-dimensional network parallel to the ab -plane. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).